Ultrahigh resolution radiation imaging system using an optical fiber structure scintillator plate - Seiichi Yamamoto (Nature Portfolio, 2018)
Abstract High resolution imaging of radiation is required for such radioisotope distribution measurements as alpha particle detection in nuclear facilities or high energy physics experiments. For this purpose, we developed an ultrahigh resolution radiation imaging system using an optical fiber structure scintillator plate. We used a ~1-μm diameter fiber structured GdAlO3:Ce (GAP) /α-Al2O3 scintillator plate to reduce the light spread. The fiber structured scintillator plate was optically coupled to a tapered optical fiber plate to magnify the image and combined with a lens-based high sensitivity CCD camera. We observed the images of alpha particles with a spatial resolution of ~25 μm. For the beta particles, the images had various shapes, and the trajectories of the electrons were clearly observed in the images. For the gamma photons, the images also had various shapes, and the trajectories of the secondary electrons were observed in some of the images. These results show that combining an optical fiber structure scintillator plate with a tapered optical fiber plate and a high sensitivity CCD camera achieved ultrahigh resolution and is a promising method to observe the images of the interactions of radiation in a scintillator.